Fаmily Vаluеs and Sоciаl Cоhеsiоn: Insights frоm Zоrоаstriаn Scripturеs - Nutfullо Nаsrullоеvich Tеshаеv (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This study aims to explore the role of family values and social cohesion as depicted in Zoroastrian scriptures, particularly focusing on the Avesta, the sacred text of Zoroastrianism, and its teachings on morality and spirituality within the family setting. The research involves an extensive analysis of the Avesta, examining its guidance on marriage, family relationships, and the upbringing of future generations. The study emphasizes the cultural, moral, and ethical principles outlined in the scriptures, highlighting their significance in fostering a virtuous and cohesive community. The Avesta underscores the importance of the family as the primary environment for moral and spiritual development, emphasizing three core principles: Good Thought (Humata), Good Word (Hukhta), and Good Deed (Hvarshta). The text details the roles and responsibilities within the family, advocating for the preservation of purity, moral integrity, and the promotion of a healthy and prosperous generation. The research finds that the Avesta provides a comprehensive framework for family dynamics, including marriage rituals, ethical standards, and the upbringing of children. The principles outlined in the Avesta are shown to be relevant even in contemporary discussions about family well-being and marital ethics. The study concludes that the teachings of the Avesta offer valuable insights into the foundational role of family in cultivating moral and spiritual growth. The principles of Good Thought, Good Word, and Good Deed remain central to fostering a virtuous and cohesive society. The Avesta's guidance on family values continues to hold significant relevance in modern times, providing a timeless framework for understanding and enhancing family dynamics and social cohesion.